Berpikir Kombinatorik: Relevansi AI dengan Model Pembelajaran Matematika - Uripno, Gusti; Yuliastuti, Rita; Nurfalah, Edy; Islami, Irma Fauztina (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2024)
This development study uses a qualitative approach and Didactic Engineering (DE) research methods. The aim of this research is to develop an AI-based learning model by combining discovery and problem based learning models involving mathematics students at PGRI Ronggolawe University, Tuban. AI or artificial intelligence is a tool that needs to be optimized in various fields, especially in the field of mathematics education. Meanwhile, mathematics education has issues related to problem solving on discrete mathematics topics. Starting from this issue, this research tries to offer a solution, the result of which is an AI-assisted blended learning model to improve combinatorial thinking. Through the combination of these models, a combination of syntax is obtained, namely: (1) Orientation; (2) Organization; (3) Exploration; (4) Execution; (5) Evaluation; (6) Generalization. This combination also considers the methods used, namely online and offline. Stages (1) and (2) are carried out offline via the LMS and quiz provider application. Meanwhile, Stages (3) and (4) were carried out involving Question AI. Stage (3) is carried out with the Geogebra alternative auxiliary application. Then stages (4) and (5) are carried out using technology-assisted presentations.